Soil nitrogen cycling under contrasting management systems in Amazon Coffea canephora agroecosystems. Issue 5 (9th August 2021) - López, Rosa Elena Ibarra; Navarrete, Eduardo F. Chávez; Rosado, Jimmy T. Pico; García, Cristian R. Subía; Margenot, Andrew J.
Abstract: Robusta coffee ( Coffea canephora Pierre ex Froehner) is well suited to the humid tropical climate of the Amazon basin. It is often produced under contrasting conditions of low‐input agroforestry systems and intensively managed monocultures that differ in N constraints on productivity. We evaluated indicators of soil N cycling and coffee plant N sufficiency using a full factorial of two input managements (organic vs. conventional) and the absence or presence of the interplanted leguminous tree (LT) Erythrina spp. in a replicated robusta coffee field trial in the Ecuadorian Amazon. Activities of soil protease, three aminopeptidases, N ‐acetyl‐β‐D‐glucosaminidase, cellobiohydrolase, and β‐glucosidase were evaluated in tandem with soil NH4 –N and NO3 –N, potentially mineralizable N (PMN), and permanganate oxidizable C (POXC), as well as coffee leaf N, leaf N/P ratio (N/P), and yield. The LT decreased soil enzyme activities, PMN, and extractable NH4 –N, as well as leaf N and leaf N/P. Enzyme activities and NH4 –N were greater under organic input, but conventional input resulted in greater PMN, leaf N, leaf N/P, and yield. Permanganate oxidizable C and NO3 –N were similar across input and interplanting but were more variable in the presence of LT relative to its absence. Lower soil enzymatic activities, labile N pools, and leaf N in coffee systems with Erythrina spp. suggest that, although a common smallholder practice in this region, interplanting this leguminous perennial has marginal impacts on soil N cycling and may not necessarily improve N supply for robusta coffee. Core Ideas: Soil N indicators evaluated for robusta coffee input system × leguminous tree interplanting. Potentially mineralizable N (PMN), leaf N, and coffee yield were greater under conventional input. Leguminous tree interplanting decreased soil N‐ and C‐enzyme activities and PMN. No relationships were found between PMN and aminopeptidase activities, nor between C‐enzyme activities and permanganate oxidizable C.